2019
DOI: 10.1002/aenm.201803548
|View full text |Cite
|
Sign up to set email alerts
|

A Stand‐Alone Si‐Based Porous Photoelectrochemical Cell

Abstract: Wireless photoelectrochemical (PEC) devices promise easy device fabrication as well as reduced losses. Here, the design and fabrication of a stand‐alone ion exchange material‐embedded, Si membrane‐based, photoelectrochemical cell architecture with micron‐sized pores is shown, to overcome the i) pH gradient formation due to long‐distance ion transport, ii) product crossover, and iii) parasitic light absorption by application of a patterned catalyst. The membrane‐embedded PEC cell with micropores utilizes a trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Adapted with permission. [ 75 ] Copyright 2019, John Wiley and Sons. c) InGaP/GaAs solar cells for the HER with their d) external quantum efficiency measurements under 1 sun illumination.…”
Section: Design and Development Of Stand‐alone Pec Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapted with permission. [ 75 ] Copyright 2019, John Wiley and Sons. c) InGaP/GaAs solar cells for the HER with their d) external quantum efficiency measurements under 1 sun illumination.…”
Section: Design and Development Of Stand‐alone Pec Cellsmentioning
confidence: 99%
“…Huskens and co‐workers reported a monolithic ion‐exchange material‐embedded PEC cell connected with triple‐junction Si cell as the light absorber, and Pt and IrO x as electrocatalysts for the HER and OER, respectively (Figure 7b). [ 75 ] It is a wireless design and reduces losses due to several wire connections, resulting in an Eff STH of up to 7%. A simulation study revealed that the proton diffusion distance between the cathode and the anode is the key parameter, and the large distance creates a pH gradient that ultimately develops an overpotential.…”
Section: Design and Development Of Stand‐alone Pec Cellsmentioning
confidence: 99%
“…A more detailed description of existing models was presented in Part I of this extended study (Bedoya-Lora et al, 2017b). • Studies of the spatial distributions of electrode kinetics through: ○ Use of louvered photoelectrodes to minimize product crossover and ohmic losses in neutral and acidic solutions (Haussener et al, 2012;Chen et al, 2014Chen et al, , 2016Jin et al, 2014;Walczak et al, 2015;Singh et al, 2017), ○ Perforating electrodes to minimize ohmic potential losses (Bosserez et al, 2016;Bedoya-Lora et al, 2017b;Hankin et al, 2017;Trompoukis et al, 2018;Vijselaar et al, 2019). • Direct experimental validation of model predictions of current density distributions across planar and perforated photoelectrodes in an up-scaled reactor (Ong et al, 2011;Carver et al, 2012;Hankin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding perforated electrodes, minimization of inhomogeneities in spatial distributions of current densities between opposing electroactive surfaces in systems 2 and 3 by means of macro-or microscopic perforations has been proposed conceptually (Orazem and Newman, 1984a;1984b), validated experimentally, and modelled for wired monopolar PECs (Hankin et al, 2017) and wireless bipolar IPECs (Bosserez et al, 2016;Trompoukis et al, 2018;Vijselaar et al, 2019). Example structures of the perforations, as well as their purpose, are illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation